Stable isotopic characterization of nitrate wet deposition in the tropical urban atmosphere of Costa Rica - Villalobos Forbes, Mario (2021)
Increasing energy consumption and food production worldwide results in anthropogenic emissions of reactive nitrogen into the atmosphere. To date, however, little information is available on tropical urban environments where inorganic nitrogen is vastly transported and deposited through precipitation on terrestrial and aquatic ecosystems. To fill this gap, we present compositions of water stable isotopes in precipitation and atmospheric nitrate (δ18O-H2O, δ2H-H2O, δ15N-NO3-, and δ18O-NO3-) collected daily between August 2018 and November 2019 in a tropical urban atmosphere of central Costa Rica. Rainfall generation processes (convective and stratiform rainfall fractions) were identified using stable isotopes in precipitation coupled with air mass back trajectory analysis. A Bayesian isotope mixing model using δ15N-NO3- compositions and corrected for potential 15N fractionation effects revealed the contribution of lightning (25.9 ± 7.1%), biomass burning (21.8 ± 6.6%), gasoline (19.1 ± 6.4%), diesel (18.4 ± 6.0%), and soil biogenic emissions (15.0 ± 2.6%) to nitrate wet deposition. δ18O-NO3- values reflect the oxidation of NOx sources via the ·OH + RO2 pathways. These findings provide necessary baseline information about the combination of water and nitrogen stable isotopes with atmospheric chemistry and hydrometeorological techniques to better understand wet deposition processes and to characterize the origin and magnitude of inorganic nitrogen loadings in tropical regions.